AN ANALYSIS OF THE DEVELOPMENT OF SIMPLE SENTENCE ACQUISTION IN 4 YEAR OLD CHILDREN - Melyana, Mita; Cintya Saepudin, Novi; Wulan Sari, Sekar; Nargis (VARIABLE RESEARCH JOURNAL, 2024)
This study explores the use of language as a communication tool, highlighting its essential role in conveying ideas, emotions, and information. Language serves not only to transmit meaning but also to express the speaker's intentions through culturally influenced vocal symbols. The research delves into the acquisition of language skills, with a particular focus on syntax, which governs sentence structure. Applied linguistics covers areas such as language acquisition, teaching methodologies, cognitive processes, and social interactions, emphasizing its interdisciplinary scope. Mastering skills like listening, speaking, reading, writing, grammar, and vocabulary is vital for effective communication. Despite the complexities in psycholinguistics and language pedagogy, systematic approaches aid in understanding and application. This research specifically investigates first language acquisition in a four-year-old child, Gadhing Danur Rendra, using qualitative descriptive methods. The study observes Gadhing's use of declarative, interrogative, imperative, and exclamative sentences, demonstrating his ability to share information, ask questions, make requests, and express feelings. The findings confirm that young children can master various sentence types, indicating healthy language development. This research enhances understanding of early language acquisition and highlights the importance of thorough language education methodologies.